Account of Robert Thompson - Thompson, Robert, 1765-
Account of sales of hay and rye by Robert Thompson to Noble Morrison, Joseph Spear, and Gen. William Thompson.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Formerly part of American Revolution miscellany.
Keywords: Morrison, Noble; Spear, Joseph; Thompson, William, -- 1736-1781.; Hay; Rye